PRINCIPLES OF DIRECTING SCIENTIFIC RESEARCHERS TO RESEARCH ACTIVITY - Otayeva Salamat Sabirovna (International Journal of Innovations in Engineering Research and Technology, 2023)
In this article, the stages of scientific research activities are analyzed, as well as important aspects of research, the content of modern requirements, ways to achieve efficiency in the process of scientific activity.